Um click na escola: imagens, produções fotográficas e influência na formação leitora e cultural dos sujeitos aprendentes nas itinerâncias do “EPA” - Penha, Gracielia Novaes da (2017)
The present research had as main goal to understand the formative potential of the visual productions in the process of reading and cultural constitution of the subjects in the Quixabeira State High School, located in the city of Quixabeira / Bahia. These productions were developed during the participation of the learning subjects in the structing project "Artistic Patrimonial Education" (EPA) promoted annually by State of Bahia’s Educational Department in their high schools. The photo books are produced with historical research and pictures of cultural patrimony (material and immaterial) of the of the subjects’ hometown, which were taken with cameras of their smartphones. This data collection was aimed with the purposes of: to analyze the visual productions (photo books), in order to understand their relevance in the reading and cultural constitution of the subject; to recognize the profile of the students who participate in the Artistic Patrimonial Education project in this school; to analyze the collected material(photo books and testimonials of the subjects), observing their socio educational and interpretive potential, from the perspective of critical understanding of visual culture; and to reflect on the process of producing the photo books in the formative processes of the learning subjects as readers and producers of meanings. This is qualitative approach research, inspired by the hermeneutic perspective, which is also used as a method of analyzing the data collected during field research. The methodological procedures performed during the research were analytical observation of photo books made in 2013, 2014 and 2015 in this state high school; a discussion meeting with the participation of ten (10) learners who were part of the project in the 2014 and 2015 editions. Semi-structured interviews with some of the subjects who participated of the EPA project, as well as with teachers of the high school who were also advisors in the project. This study is based on the theoretical field of Visual Culture, where the image is understood among the subjects as having meanings, in a critical perspective of their social roles and functions, from the simple appreciation of images to the formation of interpreters and producers of visual texts.